CD68 Antigen and Cerebral Aneurysms: A Case-Control Study - Rahmanian, Abdolkarim; Salehi, Ahmad; Kamali-Sarvestani, Eskandar; Ahrari, Iman; Mohamadhoseini, Ehsan; Jamali, Mohammad; Ghahramani, Sulmaz (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Intracranial aneurysms are more commonly associated with inflammation as a cause of their development, progression, and rupture. Macrophages and other cells can express the CD68 antigen. The aim of this study was to assess the CD68 antigen levels in cerebral aneurysm (CA) patients compared to a control group at a referral center in Iran.Methods A case-control investigation was undertaken on 88 individuals (44 of whom were cases and 44 were controls). Individuals with CA as the case group consisted of 28 ruptured and 16 unruptured subgroups. Clinical, radiographic, and CD68 levels were evaluated and registered.Results The average age of the participants was 49 years. Males comprised 43.2% of the patients, while 56.8% were females (p = 0.002). There was a statistically significant difference in the CD68 levels between the two groups. There was no significant difference (p = 0.42) between the ruptured and unruptured subgroups (23.66 and 20.47, respectively) in this comparison. No significant correlation was seen between the patients' CD68 and Glasgow Coma Scale (GCS) levels and their aneurysm diameter (p = 0.74 and 0.45, respectively). A link between CD68 levels and age was found, but it was not statistically significant (r = 0.44 and p = 0.002).Conclusions A possible involvement of CD68 as an inflammatory agent in the development of CAs but not in aneurysm rupture has been suggested. Inflammation and CD68 were positively associated with age. The CD68 antigen should be studied further in population-based cohort studies.
Keywords: cerebral aneurysm; inflammation; CD68 antigen; Iran